2011
DOI: 10.1177/1757975911422962
|View full text |Cite
|
Sign up to set email alerts
|

In search of a health education model: teachers’ conceptions in four Mediterranean countries

Abstract: School programs are defined to promote the health of the pupils and to develop their competencies so that they can adopt behaviors favorable to their health. With the European project FP6 Biohead-Citizen (2004-2007), we analyzed the conceptions of teachers as regards health education, in France, Lebanon, Morocco and Tunisia, in reference to the biomedical model and the social health model. These four countries were selected because their school curricula represented different models of health education. Lebano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…A study conducted in Morocco, evaluating the content of school textbooks in relation to health lessons, concluded that the lessons in these textbooks are inadequate, inaccurate, or out of date, and hence need improvement [17]. In Morocco, the curriculum was also primarily based on the biomedical model and included a few instructions issued from the social health model [18]. A high quality health education programme is the cornerstone of promoting healthy behaviours in the school setting.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Morocco, evaluating the content of school textbooks in relation to health lessons, concluded that the lessons in these textbooks are inadequate, inaccurate, or out of date, and hence need improvement [17]. In Morocco, the curriculum was also primarily based on the biomedical model and included a few instructions issued from the social health model [18]. A high quality health education programme is the cornerstone of promoting healthy behaviours in the school setting.…”
Section: Introductionmentioning
confidence: 99%
“…In the Biohead-Citizen project, there were 19 participating countries, where health education was primarily taught in Biology classes. Because of this, a biochemical model of health education could be detected (biology facts), and this carried a risk that the teaching emphasized biology facts rather than social and psychological elements (Caussidier, Hage, Munoz, Remki, Larribi, and Khzami;2011), although both are vital for basic and complete citizen health knowledge. Among Slovenian participants, there were significant differences in social and psychological health preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Data on teachers' attitudes and values with regard to health issues is insufficient (Pommier et al, 2009). Because of the sociocultural variables of health education (e. g. the principal ones being religion and country of residence), it is important to know teachers' perceptions about health (Caussidier et al, 2011). For example, French teachers, more than Lebanese, Moroccan or Tunisian teachers, thought that health education improved the behavior of students and developed pupils' skills (Carvalho, Clément, Bogner, and Caravita, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the teachers' conceptions were related to their individual characteristics rather than integrated into comprehensive approaches. Consequently health education implementation would require thorough training of pre-service and in-service teachers and should also explicitly take into account their conceptions and values (Caussidier et al, 2011).…”
Section: Theoretical Background Based On Review Of Literaturementioning
confidence: 99%